Disjunctive optimization design models for complex liquid-liquid multistage extractors - Reyes-Labarta, Juan A.; Grossmann, Ignacio E. (AIChE journal, 2001)
A new method for the optimal design of multicomponent liquid–liquid extraction processes using multistage countercurrent extractor systems is proposed. The method determines the optimum number of equilibrium stages and flow rates needed to obtain a specified product separation and recovery, and accounts for the possibility of side feed streams and product extractions. A superstructure is proposed that has embedded all potential configurations and interconnections. Based on this superstructure representation, the problem is formulated as an optimization problem using generalized disjunctive programming (GDP) to minimize the total cost of the process, subject to design specifications. The robustness and computational efficiency of the model is illustrated with different cases involving single and complex countercurrent cascades in a quaternary liquid–liquid system.